Slum intervention in sub-Saharan Africa: A case for New Tourist Approach - Louisa Huxtable-Thomas (African Journal of Hospitality, Tourism and Leisure, 2023)
This study queries the notion of slum as an anathema to the growth and prosperity of cities in sub-Saharan Africa. Slum tourism is discussed as an emerging intervention to address the challenge of slums in the global south. Using ethnographic account and personal reflection of 5 slum settlements and key institutions in Lusaka, a novel approach is proposed: Absolute Slum Tourism (AST) and Relative Slum Tourism (RST), to contribute to the discourse on slum interventions. The study shows that navigating informal settlements through RST approach could significantly influence urban rejuvenation, empower local narratives, giving voice to the marginalised in slum communities and promoting equity. The paper further proposes a new framework for the co-creation of slum interventions, introducing a shift in how informal urban space and residents are perceived.